An intervention to increase physical activity in care home residents: results of a cluster-randomised, controlled feasibility trial (the REACH trial). (23rd July 2021) - Forster, Anne; Airlie, Jennifer; Ellwood, Alison; Godfrey, Mary; Green, John; Cundill, Bonnie; Dawkins, Bryony; McMaster, Nicola; Hulme, Claire; Cicero, Robert; McLellan, Vicki; Graham, Liz; et al.
Abstract: Background: Care home (CH) residents are mainly inactive, leading to increased dependency and low mood. Strategies to improve activity are required. Design and setting: Cluster randomised controlled feasibility trial with embedded process and health economic evaluations. Twelve residential CHs in Yorkshire, United Kingdom, were randomised to the MoveMore intervention plus usual care (UC) ( n  = 5) or UC only ( n  = 7). Participants: Permanent residents aged ≥65 years. Intervention: MoveMore: a whole home intervention involving all CH staff designed to encourage and support increase in movement of residents. Objectives and measurements: Feasibility objectives relating to recruitment, intervention delivery, data collection and follow-up and safety concerns informed the feasibility of progression to a definitive trial. Data collection at baseline, 3, 6 and 9 months included: participants' physical function and mobility, perceived health, mood, quality of life, cognitive impairment questionnaires; accelerometry; safety data; intervention implementation. Results: 300 residents were screened; 153 were registered (62 MoveMore; 91 UC). Average cluster size: MoveMore: 12.4 CHs; UC: 13.0 CHs. There were no CH/resident withdrawals. Forty (26.1%) participants were unavailable for follow-up: 28 died (12 MoveMore; 16 UC); 12 moved from the CH. Staff informant/proxy data collection for participants was >80%; data collection from participants was <75%; at 9 months, 65.6% of residents provided valid accelerometer data; two CHs fully, two partially and one failed to implement the intervention. There were no safety concerns. Conclusions: Recruiting CHs and residents was feasible. Intervention implementation and data collection methods need refinement before a definitive trial. There were no safety concerns.